2010
DOI: 10.1016/j.phrp.2010.12.012
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological Characteristics of Scrub Typhus in Korea, 2009

Abstract: ObjectivesCurrently, the incidence of scrub typhus has increased in urban areas. In this study, we described the epidemiological characteristics of scrub typhus cases reported in the urban areas of Korea in 2009.MethodsWe analysed the case investigation reports of scrub typhus cases that were collected in Korea in 2009. Specially, the different risk factors such as fieldwork and outdoor activity were compared to urban and rural areas, and six urban cities. Statistical analysis was performed using χ2 test.Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
26
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 3 publications
2
26
0
Order By: Relevance
“…Though originally described in rural areas, there has been an increasing incidence of scrub typhus in urban areas where rodents such as mice are involved in the transmission. [2][3][4] Variations in cutaneous immunity and previous exposure to the pathogen have been considered the likely reasons for the significant differences in the frequency of eschar. 2 Gastrointestinal symptoms, lymphadenopathy, and hepatomegaly were common in our series, similar to other studies on scrub typhus from Southeast Asia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Though originally described in rural areas, there has been an increasing incidence of scrub typhus in urban areas where rodents such as mice are involved in the transmission. [2][3][4] Variations in cutaneous immunity and previous exposure to the pathogen have been considered the likely reasons for the significant differences in the frequency of eschar. 2 Gastrointestinal symptoms, lymphadenopathy, and hepatomegaly were common in our series, similar to other studies on scrub typhus from Southeast Asia.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4] Variations in cutaneous immunity and previous exposure to the pathogen have been considered the likely reasons for the significant differences in the frequency of eschar. 2 Gastrointestinal symptoms, lymphadenopathy, and hepatomegaly were common in our series, similar to other studies on scrub typhus from Southeast Asia. 5,6 However, the incidence of transaminitis was much lower in our study than in others.…”
Section: Discussionmentioning
confidence: 99%
“…Human activities include war, farming, camping, urbanization and so on. A study on the epidemiological characteristic of this disease in Korea supports this general notion [4]. …”
mentioning
confidence: 81%
“…Occupational exposure is also a significant risk factor in many countries and is particularly associated with agriculture and animal production (68% of total reported cases in South Korea, and 56·8% in Malaysia) [7][8][9][10][11]. In the Republic of Korea, rodents have been shown to be one of the major carriers of leptospirosis around swine farms; a survey in rodents conducted in 2008 found that 63·7% of rodents were infected [12,13].…”
Section: Introductionmentioning
confidence: 99%